Digital Art Gallery With Infill Development Design Approach in Medan City (EX Werenhuis Site) - Andalucia Andalucia; Syifa Azahra (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Medan is home to a number of historical buildings from the colonial era and the Islamic Malay Kingdom of Deli, many of which are now heritage sites. However, some buildings remain abandoned, such as the Warenhuis building on Jalan Hindu. Built in 1918 and protected by Law No. 11/2010 and Medan Mayor Decree No. 433/28.K/X/2021, Warenhuis needs to be revitalized to maintain its cultural significance. The COVID-19 pandemic has increased interest in digital connectivity and art. Advances in virtual reality and augmented reality have created new immersive art experiences. The 2000s saw significant growth in the field of new media art, with more and more art collectives utilizing technology. The Cultural Promotion Law No. 5/2017 focuses on the protection, development, and utilization of the arts. Medan, the third largest city in Indonesia, has great potential as a digital art gallery that helps promote culture through conservation, development and community participation. The regeneration of Warenhuis as a digital art gallery uses an infill development design that blends contemporary digital art with the classic architecture of the building, creating a dynamic and inclusive art space while maintaining its historical value.